GENETIC DIVERSITY ANALYSIS OF DATE PALM (PHOENIX DACTYLIFERA L.) IN THE KUTCHREGION OF INDIA USING RAPD AND ISSR MARKERS - Srivashtav, V. S.; Kapadia, C. V.; Mahatma, M. K.; Jha, S. K.; Jha, S.; Ahmad, T. (Emirates Journal of Food and Agriculture, 2013)
First line in abstract should be Date palm is an important fruit crop of the arid and semiarid region. In the present investigation two types of DNA based marker RAPD and ISSR were used to characterize 8 date palm genotypes grown in the Kutch region. Amplification of genomic DNA of 8 genotypes using 13 RAPD analyses yielded 88 fragments, of which 35 were polymorphic, with an average of 2.69 polymorphic fragments per primer. Two ISSR primers produced 13 bands of which 3 were polymorphic. RAPD markers were more efficient than ISSR assay with regard to polymorphic detection; RAPD markers detected 39.77% as compared to 23.07% of ISSR markers. Cluster analysis by UPGMA showed that the dendrogram obtained by RAPD and RAPD + ISSR were similar. Cluster A consisted of Early maturing, Ghanshyam and Late maturing female genotypes with 0.81 to 0.88 Jaccard's similarity range. Cluster B consisted of Seasonal female, Male-1, Male-2, Male-3 and Male-4 genotypes with 0.82 to 0.91 similarity range. Genotypes Male-1 and Male-2 were most closely related with the highest value in similarity for Jaccard's coefficient (0.91). Principal coordinate analysis differentiated one group of genotype Male-1 and Male-4 while other genotypes were randomly distributed.